Perception of individuals regarding the impact of diet on oral health during their aging process (Research, Society and Development, 2024)
Introduction: Population aging is occurring rapidly, requiring structural adjustments to meet the needs of the elderly. This is because this target group may increase the demand for health services. Objective: Identify the perception of adults and the elderly about the impact of diet on oral health during the aging process. Methods: Cross-sectional, descriptive, quantitative, and qualitative study. A questionnaire was applied to 30 participants aged between 20 and 70 years, recruited at the Comprehensive Clinic of the Universidade Federal de Pernambuco. Data collection addressed sociodemographic aspects, self-perception, and accessibility to dental and dietary services. Results: The sample consisted of adults and the elderly (50% each). Differences between the elderly and adults in terms of self-perception were identified, especially in eating habits and general health. While 73.3% of the elderly declared themselves happy, only 53.3% of adults reported satisfaction. Hypertension was identified as the most common comorbidity among the elderly. Conclusion: There is a change in self-perception during the aging process. Older people are more satisfied with their health. At any age, greater dissemination of knowledge about nutrition and oral health is necessary. The data allow for the creation of strategies for preventive health interventions, making the aging process healthier.